Mindfulness-Oriented Meditation for Primary School Children: Effects on Attention and Psychological Well-Being - Crescentini, Cristiano; Capurso, Viviana; Furlan, Samantha; Fabbro, Franco (Frontiers in Psychology, 2016)
Mindfulness-based interventions are increasingly being used as methods to promote psychological well-being of clinical and nonclinical adult populations. Much less is known, however, on the feasibility of these forms of mental training on healthy primary school students. Here, we tested the effects of a mindfulness-meditation training on a group of 16 healthy children within 7–8 years of age from an Italian primary school. An active control condition focused on emotion awareness was employed on a group of 15 age-matched healthy children from the same school. Both programs were delivered by the same instructors three times per week, for 8 total weeks. The same main teacher of the two classes did not participate in the trainings but she completed questionnaires aimed at giving comprehensive pre-post training evaluations of behavior, social, emotion, and attention regulation skills in the children. A children’s self-report measure of mood and depressive symptoms was also used. From the teacher’s reports we found a specific positive effect of the mindfulness-meditation training in reducing attention problems and also positive effects of both trainings in reducing children's internalizing problems. However, subjectively, no child in either group reported less depressive symptoms after the trainings. The findings were interpreted as suggestive of a positive effect of mindfulness-meditation on several children’s psychological well-being dimensions and were also discussed in light of the discrepancy between teacher and children’s reports. More generally, the results were held to speak in favor of the effectiveness of mindfulness-based interventions for healthy primary school children.